According to the temperature changes, it is found that:
- On Tuesday, the temperature at Noon was of -28.5 ºF.
- On Wednesday, the temperature at Midnight was of -5.5 ºF.
- On Thursday, the change was of -11.8 ºF.
- On Friday, the temperature at Noon was of -4.5 ºF.
<h3>What is the temperature change?</h3>
- The temperature change during a period is given by the <u>temperature at the end of the period subtracted by the temperature at the start of the period</u>.
On Tuesday:
- At the start of the period, the temperature was of -17.5 ºF.
- The change was of -11 ºF.
Hence:
![-11 = T_N - T_M](https://tex.z-dn.net/?f=-11%20%3D%20T_N%20-%20T_M)
![-11 = T_N + 17.5](https://tex.z-dn.net/?f=-11%20%3D%20T_N%20%2B%2017.5)
![T_N = -28.5](https://tex.z-dn.net/?f=T_N%20%3D%20-28.5)
On Tuesday, the temperature at Noon was of -28.5 ºF.
On Wednesday:
- At the end of the period, the temperature was of 10 ºF.
- The change was of 15.5 ºF.
Hence:
![15.5 = 10 - T_M](https://tex.z-dn.net/?f=15.5%20%3D%2010%20-%20T_M)
![T_M = -5.5](https://tex.z-dn.net/?f=T_M%20%3D%20-5.5)
On Wednesday, the temperature at Midnight was of -5.5 ºF.
On Thursday:
- At the end of the period, the temperature was of -24 ºF.
- At the start of the period, the temperature was of -12.2 ºF.
Hence:
![C = -24 - (-12.2) = -24 + 12.2 = -11.8](https://tex.z-dn.net/?f=C%20%3D%20-24%20-%20%28-12.2%29%20%3D%20-24%20%2B%2012.2%20%3D%20-11.8)
On Thursday, the change was of -11.8 ºF.
On Friday:
- At the start of the period, the temperature was of -21.8 ºF.
- The change was of 17.3 ºF.
Hence:
![17.3 = T_N - T_M](https://tex.z-dn.net/?f=17.3%20%3D%20T_N%20-%20T_M)
![17.3 = T_N + 21.8](https://tex.z-dn.net/?f=17.3%20%3D%20T_N%20%2B%2021.8)
![T_M = -4.5](https://tex.z-dn.net/?f=T_M%20%3D%20-4.5)
On Friday, the temperature at Noon was of -4.5 ºF.
You can learn more about change at brainly.com/question/24313700
- 30m^2 - 10m + 30
distribute your negative 10, you will first get 30m, then - 30m^2.
next distribute the negative 5, you will get - 40m, then 30.
combine like terms, and make sure its in standard form, - 30m^2 - 10m + 30
Answer:
using Pythagoras theorem
Step-by-step explanation:
it's option c
Answer:
the fist one
Step-by-step explanation: